2010
DOI: 10.2147/dddt.s10812
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin, inflammation, C-reactive protein, JUPITER, and primary prevention of cardiovascular disease – a perspective

Abstract: The major public health concern worldwide is coronary heart disease, with dyslipidemia as a major risk factor. Statin drugs are recommended by several guidelines for both primary and secondary prevention. Rosuvastatin has been widely accepted because of its efficacy, potency, and superior safety profile. Inflammation is involved in all phases of atherosclerosis, with the process beginning in early youth and advancing relentlessly for decades throughout life. C-reactive protein (CRP) is a well-studied, nonspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 389 publications
(343 reference statements)
0
97
0
6
Order By: Relevance
“…Several epidemiologic studies have demonstrated that elevated levels of CRP, pentraxin-3 (PTX3), IL-6, and soluble adhesion molecules, such as intercellular adhesion molecule-1 and VCAM-1 are associated with CVD in ESRD patients. The concept that inflammation in general, or specifically CRP, may contribute to vascular risk, was further strengthened by the Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin [26] , suggesting that decrease in high-sensitive CRP following rosuvastatin administration was associated with a substantially lower cardiovascular risk, even though cholesterol concentration was normal. In the elderly and ESRD patients on dialysis, the plasma IL-6 level is a stronger predictor of cardiovascular complications and mortality than IL-1β, TNF-α, CRP, or albumin levels.…”
Section: Cardiovascular Outcomes and Inflammation In Esrdmentioning
confidence: 99%
“…Several epidemiologic studies have demonstrated that elevated levels of CRP, pentraxin-3 (PTX3), IL-6, and soluble adhesion molecules, such as intercellular adhesion molecule-1 and VCAM-1 are associated with CVD in ESRD patients. The concept that inflammation in general, or specifically CRP, may contribute to vascular risk, was further strengthened by the Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin [26] , suggesting that decrease in high-sensitive CRP following rosuvastatin administration was associated with a substantially lower cardiovascular risk, even though cholesterol concentration was normal. In the elderly and ESRD patients on dialysis, the plasma IL-6 level is a stronger predictor of cardiovascular complications and mortality than IL-1β, TNF-α, CRP, or albumin levels.…”
Section: Cardiovascular Outcomes and Inflammation In Esrdmentioning
confidence: 99%
“…Следует отметить, что у 77% пациентов, включенных в группу приема ста-тинов, у которых в дальнейшем развился сахарный диа-бет, исходно имелось нарушение толерантности к глю-козе. В отличие от более ранних исследований, одним из критериев для участия в исследовании JUPITER яв-лялось наличие повышенного уровня высокочувстви-тельного СРБ, что также ассоциируется с возрастанием риска развития сахарного диабета [8].…”
Section: статины и риск сахарного диабетаunclassified
“…Следует отметить, что у 77% пациентов, включенных в группы статинов, у которых в дальнейшем развился СД, изначально имелось нарушение толерант-ности к глюкозе. В отличие от более ранних исследова-ний, одним из критериев для участия в исследовании JUPITER являлось наличие повышенного уровня высо-коспецифичного СРБ -провоспалительного маркера, увеличение уровня которого ассоциировано с возраста-нием риска развития СД [8].…”
Section: статины и риск развития сахарного диабетаunclassified